Haiku, Spiritual Exercises, and Bioethics - Dwyer, James (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
Pierre Hadot has discussed the deep connections between ancient Western philosophy and spiritual exercises. The author appreciates these connections, but he explains why he explored a different path. He began to write haiku as a form of spiritual practice. He wanted to use these short verses to become more mindful, present, and responsive – in his life and in his work in bioethics. After comparing traditional haiku and modern haiku, the author gives some examples from classical sources. Then he considers how reading and writing haiku might help bioethics to focus less on deliberation and choice, and more on attention and perception. Haiku might help bioethics to attend to the contexts, life conditions, and lifeworlds that shape and situate people’s lives. These short poems might even illuminate some of the backgrounds and existential grounds of ethical life. At the end, the author presents some haiku that he wrote about modern life, young children, older adults, illness, medicine, and death.